Lyme Disease Neurologic Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The neurologic manifestations and syndromes associated with Lyme disease are reported in 96 patients, ages 3 to 19 years, living on Long Island and referred to University Hospital, Stony Brook, New York.